New small firms and dimensions of economic performance - Sherrill Shaffer; Iftekhar Hasan; Mingming Zhou (Bank of Finland, 2009)
Using data from US labour market areas, we quantify empirical associations between entry by small firms and a vector of economic performance measures encompassing levels, volatilities and growth rates of several income and employment variables. Distinct and robust associations are found for net and gross rates of entry. These results suggest a richer variety of effects of entry than previously documented, and point to several potential tradeoffs associated with entry by small firms.
URN:NBN:fi:bof-20140807490
Keywords: 330